NEEDED: A RESEARCH PLAN FOR ACCOUNTANCY. - Kohler, E. L. (The Accounting Review, 1932)
Abstract The Joint Committee on Preparation for the Accounting Profession was established early in 1931 under the auspices of the American Association of University Instructors in Accounting and the American Society of Certified Public Accountants (CPA) with the hope that a means might be found of coordinating more closely the practicing and teaching professions of accounting through a study of some of their more urgent problems; the Committee was charged with the immediate responsibility of reviewing the requirements of the profession reflected in state CPA examinations. Since the first meeting of the Committee, the advice of a good many accounting instructors and professional accountants has been sought; from these conversations have arisen the conclusions not only that a study of examinations is dependent on the larger problem of preparatory training that must precede professional life, but also that preparatory training is itself dependent on the existence of adequately defined and reasonably developed professional standards.